Vitamin D Levels Predict All-Cause and Cardiovascular Disease Mortality in Subjects With the Metabolic Syndrome: The Ludwigshafen Risk and Cardiovascular Health (LURIC) study - Thomas, G. Neil; ó Hartaigh, Bríain; Bosch, Jos A; Pilz, Stefan; Loerbroks, Adrian; Kleber, Marcus E; Fischer, Joachim E; Grammer, Tanja B; Böhm, Bernhard O; März, Winfried (Diabetes care, 2012)
OBJECTIVE: Optimal vitamin D levels are associated with reduced cardiovascular and all-cause mortality. We investigated whether optimal 25-hydroxyvitamin D (25[OH]D) is protective in individuals with the metabolic syndrome. RESEARCH DESIGN AND METHODS: The Ludwigshafen Risk and Cardiovascular Health (LURIC) study is a cohort study of subjects referred for coronary angiography between 1997 and 2000, from which 1,801 with the metabolic syndrome were investigated. Mortality was tracked for a median of 7.7 years. Multivariable survival analysis was used to estimate the association between 25(OH)D levels and mortality. RESULTS: Most subjects (92%) had suboptimal levels of 25(OH)D (<75 nmol/L), with 22.2% being severely deficient (<25 nmol/L). During follow-up, 462 deaths were recorded, 267 (57.8%) of which were cardiovascular in origin. After full adjustment, including the metabolic syndrome components, those with optimal 25(OH)D levels showed a substantial reduction in all-cause (hazard ratio [HR] 0.25 [95% CI 0.13–0.46]) and cardiovascular disease mortality (0.33 [0.16–0.66]) compared with those with severe vitamin D deficiency. For specific cardiovascular disease mortality, there was a strong reduction for sudden death (0.15 [0.04–0.63]) and congestive heart failure (0.24 [0.06–1.04]), but not for myocardial infarction. The reduction in mortality was dose-dependent for each of these causes. CONCLUSIONS: Optimal 25(OH)D levels substantially lowered all-cause and cardiovascular disease mortality in subjects with the metabolic syndrome. These observations call for interventional studies that test whether vitamin D supplementation provides a useful adjunct in reducing mortality in these subjects.